ANALISIS AKTIVITAS FISIK DAN KESEIMBANGAN PADA SISWA SMP MELALUI PERMAINAN EGRANG SEBAGAI AKTIVITAS KEOLAHRAGAAN BERBASIS BUDAYA LOKAL - Mohammad Fatra Tomagola; La Robi; Fadly Kelubas; Lutfi Hulihulis; Fatma Wati Rumakey (STKIP Subang, 2026)
Traditional games are a form of physical activity based on local culture that has great potential to be developed in physical education learning. One traditional game that is still widely known and played in various regions of Indonesia is the egrang (stilt-walking) game, which requires physical activity and body balance skills. This study aims to analyze physical activity and balance in the egrang game as a local culture-based physical activity among eighth-grade junior high school students. This study used a quantitative approach with a descriptive-analytic method and a cross-sectional design. The research subjects consisted of 37 eighth-grade junior high school students selected using a total sampling technique. Physical activity was measured through heart rate before and after playing the egrang game, while balance was measured using static and dynamic balance tests. Data analysis was conducted using descriptive statistics, including mean, standard deviation, minimum, and maximum values. The results showed an increase in heart rate after playing the egrang game, indicating engagement in physical activity with light to moderate intensity. In addition, the balance measurements indicated that students had good static and dynamic balance abilities, with a dominance in dynamic balance. These findings suggest that the egrang game not only holds cultural value but also has potential as an effective physical activity to improve students’ physical activity levels and balance. Therefore, the egrang game is suitable to be utilized as an alternative in physical education learning that is contextual, meaningful, and based on local culture.